Status of fisheries in Gaza Strip - Hussein, Doaa M. A. (International journal of Euro-Mediterranean studies, 2022)
This paper comprehensively portrays fisheries' past trends and current status in the Gaza Strip, relying on the literature review and own data collection. Gaza is a politically contested territory that has not been the subject of a targeted analysis with the view to shaping measures for more effective fisheries management. In order to contribute to this, the article first discusses gaps that may impede effective management and then highlights future challenges. Total seafood production has grown steadily overall in the last 15 years due to the rapid growth of aquaculture alongside an increase in fisheries production (87%) from 1995 to 2020. The fishing fleet of the Gaza Strip increased by 269%, from 647 motorized vessels in 1995 to 1741 vessels in 2020. Gillnets, trammel nets, longlines, purse seine nets, and driftnet were the fishing gear most used by motorized vessels, followed by trawlers. Despite efforts through national legislation to address fishery management problems, weak enforcement, low compliance, and unregulated fishing remain a serious challenge. Fisheries stakeholders, including funders of development aid to Gaza, have to consider the social and political context of these fisheries when developing suitable management strategies.
Keywords: acquaculture; Akvakultura; fisheries; fisheries management; Gaza Strip; Gospodarski ribolov; Oskrba s hrano; ribištvo; samooskrbni ribolov; subsistence fisheries; upravljanje ribolova